2018
DOI: 10.5604/01.3001.0011.7481
|View full text |Cite
|
Sign up to set email alerts
|

Sea-buckthorn (Hippophae rhamnoides L.) as a source of compounds with antitumor and radioprotective activity

Abstract: This work presented characteristics of sea buckthorn (H. rhamnoides), the bioactive compounds they contain and their pro-health, anti-cancer and radioprotective activity. Studies have shown that antioxidants contained in the fruits of plant, such as vitamins A, E and phenolic compound, reduce oxidative damage and also inhibit the formation of carcinogenic compounds, such as aflatoxin B1 or N-nitrosamide. Bioactive substances included in sea buckthorn inhibit the growth and proliferation of malignant cells in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Management of the fungal microorganisms present on the surface of berries might be a powerful instrument for control of phytopathogenic and potentially antagonistic microorganisms affecting development and quality of the berries.Cultivation of sea buckthorn is developing due to the request for its berries with a high content of minerals, different vitamins, specific valuable oils, phenolics, and essential fatty acids, as well as low level of both fructose and glucose [5]. Phytochemicals and essential oil generated from sea buckthorn berries and seeds reduce inflammation; have antibacterial, anticancer, and radioprotective activity; relieve pain; and promote regeneration of tissues [3,6,7].The microenvironments coherent with plants and fruits are highly colonized by different communities of bacterial and fungal microorganisms [8]. Plants provide nutrient-rich and stable surrounding conditions vital for the development of microbiota.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Management of the fungal microorganisms present on the surface of berries might be a powerful instrument for control of phytopathogenic and potentially antagonistic microorganisms affecting development and quality of the berries.Cultivation of sea buckthorn is developing due to the request for its berries with a high content of minerals, different vitamins, specific valuable oils, phenolics, and essential fatty acids, as well as low level of both fructose and glucose [5]. Phytochemicals and essential oil generated from sea buckthorn berries and seeds reduce inflammation; have antibacterial, anticancer, and radioprotective activity; relieve pain; and promote regeneration of tissues [3,6,7].The microenvironments coherent with plants and fruits are highly colonized by different communities of bacterial and fungal microorganisms [8]. Plants provide nutrient-rich and stable surrounding conditions vital for the development of microbiota.…”
mentioning
confidence: 99%
“…Cultivation of sea buckthorn is developing due to the request for its berries with a high content of minerals, different vitamins, specific valuable oils, phenolics, and essential fatty acids, as well as low level of both fructose and glucose [5]. Phytochemicals and essential oil generated from sea buckthorn berries and seeds reduce inflammation; have antibacterial, anticancer, and radioprotective activity; relieve pain; and promote regeneration of tissues [3,6,7].…”
mentioning
confidence: 99%
“…Both in vitro and human and animal in vivo studies on sea buckthorn have found a range of bioactive chemicals in its leaves, roots, seeds, and berries, known as seaberry, or Siberian pineapple, as well as the oil extracted from them; these compounds exhibit a wide range of anti-inflammatory, anticancer, antioxidant, and anti-atherosclerotic activities (Zeb, 2006 ; Basu et al, 2007 ; Kumar et al, 2011 ; Suryakumar and Gupta, 2011 ; Xu et al, 2011 ; Christaki, 2012 ; Teleszko et al, 2015 ; Olas, 2016 ; Ulanowska et al, in press ). Several trace elements and vitamins (especially A, C, and E), lipids, carotenoids, amino acids, unsaturated fatty acids, and phenolic compounds that are found in the berries are presented in Table 1 (Olas, 2016 ; Gradt et al, 2017 ; Ulanowska et al, in press ). Their concentration in the berries depends on the climate, size, maturity of the plant, and the procedure used to process and store the plant material (Fatima et al, 2012 ; Malinowska and Olas, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Its berry pulp can obtain phytochemicals and essential oil, and seeds can have an anticancer, antibacterial effect, and radio protective activity. 3 Sea buckthorn leaves are also rich in important antioxidants, such as flavonoids, vitamins, catechins, and beta-carotene. 4 Thus, sea buckthorn is considered an important economic and ecological tree.…”
Section: Introductionmentioning
confidence: 99%
“…Sea buckthorn fruit with high vitamin C contents is a rich nutritious berry 1,2 . Its berry pulp can obtain phytochemicals and essential oil, and seeds can have an anticancer, antibacterial effect, and radio protective activity 3 . Sea buckthorn leaves are also rich in important antioxidants, such as flavonoids, vitamins, catechins, and beta‐carotene 4 .…”
Section: Introductionmentioning
confidence: 99%